The Representation of the Hedgehog Goddess Abaset at Bahariya Oasis - Sherbiny, Hend.
The representation of the hedgehog goddess Abaset in ancient Egyptian iconography is unique. The goddess appears twice on the decorated walls of the tomb of the wealthy Saite merchant, Bannentiu, at Qarat Qasr Salim, Bahariya Oasis. Reading and analysis of the two scenes of this goddess are presented.